Analisis Kebutuhan terhadap Kecerdasan Wirausaha Pada Mahasiswa Politeknik Bosowa - Burhan, Imron; Ilham, Ilham (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
This study aims to analyze the level of needs of Bosowa Polytechnic students on entrepreneurial intelligence. The research approach used in this study is a quantitative descriptive approach. The research data was collected using a questionnaire instrument with a Likert scale to measure the level of needs of Bosowa Polytechnic students on entrepreneurial intelligence. The results of the study of 171 respondents of the Bosowa Polytechnic students showed that as many as 81.87% of students were in dire need of an entrepreneurial intelligence guide and 18.12% of students needed an adequate guide to entrepreneurial intelligence. This shows that Bosowa Polytechnic students are in dire need of an increase in entrepreneurial intelligence. Based on the results of the study of literature, a draft format for guiding the improvement of entrepreneurial intelligence consists of two indicators, namely (1) self-management skills (Interpersonal Skill); (2) The ability to interact with others (Intrapersonal Skill)